Die spanisch-amerikanische Jesuitenuniversität in Córdoba, Argentinien Transatlantische Verflechtungen und gesellschaftliche Verankerung in der Kolonialzeit - Aranha, Patricia (Historamericana, 2022)
The book examines the Spanish-American Jesuit University in Córdoba, Argentina, from a transatlantic perspective. It shows how staff was specifically recruited from several continents, how the university also conducted research in addition to teaching, and how care was taken in the student body to reflect the breadth of society.